1981
DOI: 10.1007/bf02370034
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature and nitrate on vegetative growth and nitrogen accumulation by nodulated soybeans

Abstract: Acetylene reduction growth rate KEY WORDSGlycine max (L.) Merrill Leaf number N 2 fixation Relative SUMMARY Inoculated soybeans [Glycine max (L.) Merrill] were grown in controlled environments to evaluate the relationship between temperature and applied NO3-N on growth rates, N accumulation, and acetylene reduction activity during the vegetative growth stage. Soybeans were grown at day/night temperatures of 22/18 and 26/22~ in sand culture with daily applications of 21.4 mM (high) and 2.1 mM (low) NO3-N in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Imsande (1989), however, reported that N2 fixation during soybean podfill enhances seed yield compared to urea N assimilation. Other reports indicate that soybean grown in solution c ulture supplied with mineral N assimilates substantially more N than do modulated plants (Jones et al, 1981;Lathwell and Evans, 1951;Wych and Rains, 1979). Similar results have been reported only rarely from field experiments (Cassman et al, 1981;Thies et al, 1991).…”
supporting
confidence: 70%
“…Imsande (1989), however, reported that N2 fixation during soybean podfill enhances seed yield compared to urea N assimilation. Other reports indicate that soybean grown in solution c ulture supplied with mineral N assimilates substantially more N than do modulated plants (Jones et al, 1981;Lathwell and Evans, 1951;Wych and Rains, 1979). Similar results have been reported only rarely from field experiments (Cassman et al, 1981;Thies et al, 1991).…”
supporting
confidence: 70%
“…In practice a primary 'starter' dose of inorganic N has been found to improve the growth of a range of leguminous species e.g. pea (Oghoghorie and Pate 1971) and soybean (Jones et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases it has been found that seed N reserves are sufficient to last the young plants until nodules begin actively to fix nittogen (for exatnple Pi.sum arvense; Pate, 1958a). In other cases a period of N stress has been observed before nodules fix nitrogen (for example, Jones, Patterson & Raper, 1981;Hildebrand, Harper & Hymowitz, 1981, for Glycine max;Cookson, Hughes & Cootnbs, 1980;Fratico & Munns, 1982 for Pha.seolus vulgari.s). This has led to the practice of giving a dose of 'starter N' fertilizer, although in tnany tetnperate soils mineralization of organic nitrogen takes place when soil temperatures rise in spring (if sufficient soil moisture is available) and provides such a dose naturally (see also discussion in Sprent et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the C is in a highly reduced form (fat), and can apparently provide sufTieient energy to support growth of the young seedling since, after emergence, N is considered to be tnore limiting than C (Williams, De,Iong & Phillips, 1981). However, the extent of such a nitrogen limitation is environmentally conditioned, as the data of Jones et al (1981) show. Of the various temperature regimes used, one of 26/22 °C day/night led to a depletion of eotyledonary Table 1A, Areas of leaves al the lower nodes of three grain legumes.…”
Section: Introductionmentioning
confidence: 99%